2015
DOI: 10.1016/j.nimb.2015.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of real photon diffraction on parametric X-ray radiation angular distribution in thin perfect crystals

Abstract: Measurements of an electron beam parameters a b s t r a c tUsing the previously proposed method of calculating diffracted photon yields in thin perfect crystals, analyzed a relative contribution of parametric X-ray radiation and diffracted photons in thin crystals. It is shown that for average energy of electrons and the center of the PXR spot diffracted real photon contribution is comparable to the yield of parametric X-ray radiation and determines the shape of the angular distribution of the total emission i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…As noted in Ref. [24] and confirmed in Refs. [25,26], for an electron energy above several GeV, the contribution of the DTR at the center of the reflex becomes significantly greater than the contribution of the PXR, and the resulting angular distribution of the radiation yield varies significantly.…”
Section: Proposed Measurement Techniquesupporting
confidence: 82%
“…As noted in Ref. [24] and confirmed in Refs. [25,26], for an electron energy above several GeV, the contribution of the DTR at the center of the reflex becomes significantly greater than the contribution of the PXR, and the resulting angular distribution of the radiation yield varies significantly.…”
Section: Proposed Measurement Techniquesupporting
confidence: 82%
“…It has been reported that for electrons with an energy of several tens of GeV, the angular density of emission intensity at the center of the diffraction spot is much lower for PXR with a dip width of several mrad for this observation angle than for DTR with the characteristic emission angle about −1 concentrated near the Bragg's direction [13,14,21]. Because of the same nature of volume and surface emissions, we may expect a similar relationship between surface PXR and DDR.…”
Section: Theoretical Considerationsmentioning
confidence: 70%
“…As shown in [16] and was confirmed in [17,18], the contribution of transition-radiation diffraction at the reflection center becomes much larger than that of PXR as the electron energy increases to 5 GeV. For an electron energy of 10 GeV, the angular density of DTR exceeds that of PXR by a factor of 500 or more because of a sharp decrease in the characteristic radiation angle determining the angular distribution of the transition radiation, and, consequently, of DTR.…”
Section: We Assume Thatmentioning
confidence: 73%
“…The presence of the bright peak in the angular radiation distribution [16,23], whose form is like that of the angular PXR distribution, in Figs. 1 and 3, makes it possible also to use the above procedure to determine the dimensions of a high-energy electron beam.…”
Section: We Assume Thatmentioning
confidence: 75%